PENGGUNAAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 3 SD PADA MATERI MENGENAL SIKLUS PADA MAKHLUK HIDUP - Nurhayati (Jurnal Ilmiah Mandalika Education (MADU), 2023)
This research aims to evaluate the implementation of Project-Based Learning (PjBL) to enhance the learning outcomes of third-grade elementary school students on the topic of understanding life cycles in living organisms. The research methodology employed is Classroom Action Research (CAR), involving 15 students as participants. The PjBL learning process is conducted in two cycles with structured steps, including determining main questions or issues, planning the project, scheduling project completion, monitoring progress, presenting project results, and evaluating the project process and outcomes. Data analysis involves comparing pre-test and post-test results in each cycle.The results of the research indicate a significant improvement in students' understanding of the "Understanding Life Cycles in Living Organisms" topic after implementing PjBL. In the first cycle, there was a 25% increase, and in the second cycle, an additional 15% increase was observed. Furthermore, students exhibited high engagement and a positive response to PjBL learning.In conclusion, this research affirms that the Project-Based Learning (PjBL) model is effectively utilized to enhance students' learning outcomes. Additionally, the PjBL learning process, employing a project cycle approach, has proven to have a significant positive impact on students' understanding. The improvement in test scores in each cycle reflects the success of implementing PjBL as an engaging and effective alternative learning method at the elementary school level.